2014
DOI: 10.2147/bctt.s71781
|View full text |Cite|
|
Sign up to set email alerts
|

BP-C1 in the treatment of patients with stage IV breast cancer: a randomized, double-blind, placebo-controlled multicenter study and an additional open-label treatment phase

Abstract: The aims were to compare the efficacy and tolerability of a new benzene-poly-carboxylic acids complex with cis-diammineplatinum (II) dichloride (BP-C1) versus placebo and to investigate the long-term tolerability of BP-C1 in the treatment of patients with metastatic breast cancer.Material and methodsA randomized, double-blind, placebo-controlled multicenter study was performed with a semi-crossover design. Patients allocated to placebo switched to BP-C1 after 32 days of treatment. Patients who completed 32 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…A Phase I study demonstrated the clinical therapeutic benefit of BP-C1 in MBC, 11 as did a Phase II randomized, double-blind, placebo-controlled, multicenter study with semi-crossover design. 12 When 0.035 mg/kg BP-C1 was delivered intramuscularly for 32 days, it was found effective and also safe to use. Patients who completed 32 days of BP-C1 treatment were offered to continue BP-C1 (ie, open-label use) for an additional 32 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Phase I study demonstrated the clinical therapeutic benefit of BP-C1 in MBC, 11 as did a Phase II randomized, double-blind, placebo-controlled, multicenter study with semi-crossover design. 12 When 0.035 mg/kg BP-C1 was delivered intramuscularly for 32 days, it was found effective and also safe to use. Patients who completed 32 days of BP-C1 treatment were offered to continue BP-C1 (ie, open-label use) for an additional 32 days.…”
Section: Discussionmentioning
confidence: 99%
“…Prospectively collected laboratory results were obtained from 47 patients suffering from stage IV MBC, in two controlled clinical trials of daily intramuscular (IM) BP-C1 treatment for 32 days. 11 , 12 Study 1 was performed as an open, nonrandomized, Phase I dose–response, multicenter study with a three-level, between-patient, response surface pathway (RSP) design. 13 Of the 47 MBC patients, 15 were of Asian origin.…”
Section: Methodsmentioning
confidence: 99%
“…BP-C1 contains a benzene-poly-carboxylic acid complex with cis -diammineplatinum (II) dichloride, inducing apoptosis in human breast cancer cells 15. Previous studies with BP-C1 in the treatment of MBC patients have shown that tumor growth decreased without causing extra toxicity,14,16 although mainly manageable mild-to-moderate transient side effects may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum containing antineoplastic investigational medicinal product (IMP) BP-C1 is at the moment on the stage of clinical trials in patients with metastatic breast cancer [ 15 ]. Investigational medicinal product BP-C2 is a composition of BP-Cx-1 with ammonium molybdate.…”
Section: Introductionmentioning
confidence: 99%